Causalidade e inferência em David Hume e Charles Sanders Peirce - Montenegro, Christian Emmanuel de Menezes (2015)
This paper aims to achieve a study of the conceptions of causality in David Hume, a Scottish empiricist philosopher of the 18th century and in Charles Sanders Peirce, an American pragmatist philosopher of the 19th century. In order to discuss these conceptions, a historical-critical approach was chosen. We believe this approach should enable the reader a clearer perception of what is at stake, namely, the passage of a deterministic vision for an indeterministic worldview. Hence we will take a route we intend to present the modern scientific thinking from its genesis to mid 20th century. As Michel Paty tells us in his article entitled The genesis of physical causality2, (published in the journal Studia Scientiae): the notions or categories of causality and determinism have accompanied the formation of modern sciences, foremost, the Physical Science one . At the time of Galileo, Descartes and Newton, physics was called Natural Philosophy and comprised a search laws of Nature expressed through regularities and causal relations. Although the notion or idea of causality were always present in Western Thought since Greek times it could be mainly found merged with metaphysical conceptions. Aristotle, for example, in his work entitled Metaphysics, lists four causes, namely, material cause, formal cause, efficient cause and final or teleological cause. According to Paty, it was due to d Alembert s Traité de dynamique more than Newton s Principia the idea of a physical causality subsumed to a mathematical functional relation (differential temporal causality), in the sense of efficient cause, that took shape. It was this conception, excluding other causes, says Paty, that prevailed in Modern Science, from the 18th century, Hume s time. The success achieved by Newtonian synthesis, expressed in its analytical form by d Alembert, led to the belief in determinism, expressed in Laplace s saying. With the advent of the theory of evolution by natural selection in the biological sciences of the 19th century, many thinkers considered that living being built up as something irreducible, which could not be explained solely in terms of efficient cause, therefore it would be necessary to resort to some kind of life force or vital breath inflated by an intelligent intention and only by him. Hence the need to resort to the final or teleological causes. Peirce was one of these thinkers, as we will have the opportunity to see along the exposition of his philosophy. We take as theoretical basis of our research the following works: 2 PATY, Michel. The genesis of physical causality . In Scientiae Studia, São Paulo, vol. 2, n. 1, 2004, p. 9. Available in www.scielo.br/scielo.php?pid=S1678-31662004000100002&script. X A Treatise of Human Nature, Enquiries Concerning Human Understanding and the Principles of Moral and An Abstract of a Treatise of Human Nature by David Hume, besides the works of two commentators, namely, The Hume s Skepticism by Plínio Junqueira Smith and Hume and the Epistemology by João Paulo Monteiro. In the same way, Regarding Peirce s works, we have taken the following works: The Essential Peirce, vol. 1; The Essential Peirce, vol. 2; Illustrations of the Logic of Science; Semiotics; Semiotics and Philosophy and the works by three commentators, namely, Kósmos Noetós by Ivo Assad Ibri; The Induction from Aristotle to Peirce, by Maria de Lourdes Bacha; Charles S. Peirce s Evolutionary Philosophy by Carl Hausman